Frontal fibrosing alopecia and lichen planus pigmentosus: diagnosis and therapeutic challenge - Fabiane Andrade Mulinari-Brenner; Marina Riedi Guilherme; Murilo Calvo Peretti; Betina Werner (Sociedade Brasileira de Dermatologia, 2017)
Abstract Frontal fibrosing alopecia is a variant of lichen planopilaris with marginal progressive hair loss on the scalp, eyebrows and axillae. We report a case of frontal fibrosing alopecia and lichen planus pigmentosus in a postmenopausal woman, that started with alopecia on the eyebrows and then on the frontoparietal region, with periocular and cervical hyperpigmentation of difficult management. The condition was controlled with systemic corticosteroid therapy and finasteride. Lichen planus pigmentosus is an uncommon variant of lichen planus frequently associated with frontal fibrosing alopecia in darker phototipes. It should be considered in patients affected by scarring alopecia with a pattern of lichen planopilaris and areas of skin hyperpigmentation revealing perifollicular hyperpigmentation refractory to multiple treatments. This case illustrates diagnostic and therapeutic challenge in face of scarring alopecia and perifollicular hyperpigmentation.